2012
DOI: 10.1189/jlb.0512242
|View full text |Cite
|
Sign up to set email alerts
|

Immature murine NKT cells pass through a stage of developmentally programmed innate IL-4 secretion

Abstract: We assessed the production of the canonical Th2 cytokine IL-4 by NKT cells directly in vivo using IL-4-substituting strains of reporter mice that provide faithful and sensitive readouts of cytokine production without the confounding effects of in vitro stimulation. Analysis in naïve animals revealed an "innate" phase of IL-4 secretion that did not need to be triggered by administration of a known NKT cell ligand. This secretion was by immature NKT cells spanning Stage 1 of the maturation process in the thymus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
3
14
0
1
Order By: Relevance
“…We found that up to 40% of thymic iNKT cells in BALB/c-KN2 mice expressed hCD2 on the cell surface, whereas B6 iNKT cells from B6-KN2 mice were largely hCD2 negative (Fig. 1a), consistent with a recent report 11 . In young BALB/c-KN2 mice, there was a >10 fold increase in the number of hCD2 positive cells in the thymus compared to B6-KN2 mice (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that up to 40% of thymic iNKT cells in BALB/c-KN2 mice expressed hCD2 on the cell surface, whereas B6 iNKT cells from B6-KN2 mice were largely hCD2 negative (Fig. 1a), consistent with a recent report 11 . In young BALB/c-KN2 mice, there was a >10 fold increase in the number of hCD2 positive cells in the thymus compared to B6-KN2 mice (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Dickgreber and colleagues suggested that “innate IL-4” is secreted from immature iNKT cells 11 . However, based on our findings of distinct transcription factors expressed in iNKT subsets, we considered an alternative “lineage diversification” model for iNKT cells 9 , analogous to effector T helper cell 16 and innate lymphoid cell 29 differentiation (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that immature iNKT cells in stages 1 and 2 express higher levels of PLZF compared with more mature iNKT cells 26,27 , and are more potent producers of IL-4 (refs 46,47). An alternative view is that some of these tetramer + but NK1.1-negative cells are not immature, but are fully differentiated to a so-called NKT2 subset that responds to IL-25 and that preferentially produces Th2 cytokines 48 .…”
Section: Resultsmentioning
confidence: 99%
“…To delineate the exact location of iNKT cell activation and effector cytokine production, we used IL-4 dual reporter (4get/KN2)(24) and IFNγ reporter (Great)(25) mice. iNKT cells from 4get/KN2 mice are constitutively GFP+ due to persistent expression of IL-4 mRNA(26) and, upon activation, rapidly express huCD2 on their cell surface indicating IL-4 protein production(24, 27). Following intravenous αGalCer administration, splenic CD1d-tetramer+ iNKT cells began to express huCD2 at 2 hours with peak production occurring at 4 hours post-immunization (Fig.…”
Section: Resultsmentioning
confidence: 99%